Effects of silver-graphene oxide on seed germination and early growth of crop species - Kim, Min-Ji (PeerJ, 2020)
Due to its excellent material properties, silver-graphene oxide (Ag-GO) is being studied for diverse applications, such as antimicrobial agents, catalysts and absorbents. Such use of Ag-GO may lead to its release into terrestrial ecosystems, but little is known about the impact of Ag-GO on plants. In the present study, we determined the effects of Ag-GO on seed germination and early growth of crop species by analyzing the germination rate, growth of roots and shoots, hydrogen peroxide (H(2)O(2)) accumulation, and the uptake of Ag in alfalfa, radish and cucumber treated with 0.2–1.6 mg mL(−1) of Ag-GO. Ag-GO treatment increased the shoot growth of radish at 0.2–1.6 mg mL(−1) but decreased that of cucumber at 0.8 mg mL(−1). In addition, Ag-GO enhanced the root elongation of radish at 0.2 mg mL(−1) but inhibited that of alfalfa at 0.2, 0.8 and 1.6 mg mL(−1). Ag-GO treatment induced H(2)O(2) production in alfalfa, radish and cucumber in a concentration-dependent manner. Larger amounts of Ag accumulated in the seedlings as the concentration of Ag-GO increased, and such accumulation suggests that Ag may be transferred to higher trophic levels when plants are exposed to Ag-GO in ecosystems. Our study can, thus, serve as an important basis for setting guidelines for the release of nanomaterials into the environment.